2011
DOI: 10.7150/ijbs.7.1171
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobium Chlorophenolicum Dichlorohydroquinone Dioxygenase (PcpA) Is Alkaline Resistant and Thermally Stable

Abstract: Dichlorohydroquinone dioxygenase (PcpA) is the ring-cleavage enzyme in the PCP biodegradation pathway in Sphingobium chlorophenolicum strain ATCC 39723. PcpA dehalogenates and oxidizes 2,6-dichlorohydroquinone to form 2-chloromaleylacetate, which is subsequently converted to succinyl coenzyme A and acetyl coenzyme A via 3-oxoadipate. Previous studies have shown that PcpA is highly substrate-specific and only uses 2,6-dichlorohydroquinone as its substrate. In the current study, we overexpressed and purified rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Purified PcpA lost activity in a time‐dependent manner (Supplementary Fig. S1) by autoxidation of Fe(II) to Fe(III) (Xun et al ., ; Sun et al ., ), which could be completely recovered in 48 h by reduction with 100 μM ascorbic acid. PcpA recovered from crystals that were dissolved in solution were found to be catalytically inactive, but regained full activity after reduction by ascorbic acid (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified PcpA lost activity in a time‐dependent manner (Supplementary Fig. S1) by autoxidation of Fe(II) to Fe(III) (Xun et al ., ; Sun et al ., ), which could be completely recovered in 48 h by reduction with 100 μM ascorbic acid. PcpA recovered from crystals that were dissolved in solution were found to be catalytically inactive, but regained full activity after reduction by ascorbic acid (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PcpA uses Fe(II) for catalysis (Xun et al ., ; Sun et al ., ) which is partially oxidized to Fe(III) during purification (Xun et al ., ; Sun et al ., ). Purified PcpA lost activity in a time‐dependent manner (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of two peaks in pH profile was confirmed by repeating the experiment multiple times under finer grids around pH 8.0. This double-peak peaks [31]. However, it has been reported that BGs from the termite N. takasagoensis, N. koshunensis, and C. formosanus are most active at pH 5.0-5.5 and inactivated at extreme pH (<3.0 or >8.0) [15,19,29,32].…”
Section: Discussionmentioning
confidence: 95%
“…PcpA protein contains a nonheme Fe atom and has no homology with classical ring-fission enzymes such as catechol dioxygenase. The enzyme is able to catalyze the ring-opening of a wide range of substituted hydroquinones [60, 63, 64]. In spite of the detailed knowledge of the PcpA enzyme from S. chlorophenolicum , other putative members of the family are present in several gram-negative bacteria (Figure 3).…”
Section: Degradation Of Hydroquinone Under Aerobic Conditionsmentioning
confidence: 99%